2012
DOI: 10.2494/photopolymer.25.723
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stress Effect on Ionic Conductivity of Perflurosulfonic Acid (PFSA) Film by Photolithography

Abstract: Direct Methanol Fuel Cell (DMFC) consists of a perflurosulfonic acid (PFSA) electrolyte is attractive as a portable power source. It is possible to fabricate a DMFC array by dividing a PFSA film into micro pieces by photolithography. In this regard, it is known that photoresist film causes significant compressive and tensile stress generation in an underlying layer. Then it is needed to control preparation condition of photoresist film formed on a PFSA film. The effect of compressive load in a PFSA film is obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Numerous studies on optimizing the assembly procedure (such as bolt assembly), especially for the homogenization of the arising mechanical stresses have been reported [126]. A study on the mechanical response of membrane subjected to various clamping conditions observed the formation of pinhole at the center of the membrane which is due to the extreme form of non-uniformity in this constraint configuration [127]. One study observed that clamping stress is conducive to the durability and integrity of the membrane that, however, depends on the design specifications [128].…”
Section: Stack Assembly Effectsmentioning
confidence: 99%
“…Numerous studies on optimizing the assembly procedure (such as bolt assembly), especially for the homogenization of the arising mechanical stresses have been reported [126]. A study on the mechanical response of membrane subjected to various clamping conditions observed the formation of pinhole at the center of the membrane which is due to the extreme form of non-uniformity in this constraint configuration [127]. One study observed that clamping stress is conducive to the durability and integrity of the membrane that, however, depends on the design specifications [128].…”
Section: Stack Assembly Effectsmentioning
confidence: 99%
“…Several groups have made micro fuel cells integrated on various substrates as a chip scale power source [2][3][4][5]. The authors have reported a fuel cell formed on a PFT film substrate [6]. In this case, semiconductor fabrication process was commonly employed for the multilayer structure fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…They formed micro channels of 100µm width and 10µm depth on the PFSA film. The authors have discussed that an effect of photoresist film stress on the photoresist/PFSA double layer structure [5].…”
Section: Introductionmentioning
confidence: 99%